2020
DOI: 10.4236/ojog.2020.1020029
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault: Epidemiological Profile and Clinical Aspects at the Brazzaville University Hospital Center

Abstract: Objective: to identify the socio-demographic profile of the alleged victims of sexual assault, to define the characteristics of the aggressors, to describe the types of clinical lesions, and to analyze the link between these different parameters. During the study period, 5620 clients were admitted to gynecological emergencies, including 150 for sexual assault (2.6%). The alleged victims of aggression were 14 years old on average [range: 2-49 years]. Among these clients, there were 147 (98%) women and 3 (2%) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…This is similar to a study conducted at Gandhi Memorial Hospital in Addis Ababa, Ethiopia (87.8%); 13 Lagos State University Teaching Hospital, Nigeria (83.5%); 15 and University Hospital Brazzaville, Congo (83%). 17 But the current finding is higher than the study conducted in Kenya (76%). 18 The psychological complications of sexual assault carried out by assailants known to survivors could result in more damaging outcomes than being assaulted by a stranger.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…This is similar to a study conducted at Gandhi Memorial Hospital in Addis Ababa, Ethiopia (87.8%); 13 Lagos State University Teaching Hospital, Nigeria (83.5%); 15 and University Hospital Brazzaville, Congo (83%). 17 But the current finding is higher than the study conducted in Kenya (76%). 18 The psychological complications of sexual assault carried out by assailants known to survivors could result in more damaging outcomes than being assaulted by a stranger.…”
Section: Discussioncontrasting
confidence: 67%
“…Unlike other hospital-based studies, 3,6,13,17 in this study there was a patient who died from complications (genital and non-genital injuries) of sexual assault. There were also cases with severe forms of physical injuries, including rectovaginal fistula and fracture.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In Nancy, France, Kolopp et al [20] found a mean age of 23.9 years in 2017. This average age is higher than those found by other authors: Enouani et al [6] in Brazzaville in 2020 (average age: 14 years); Khemakhem et al [21] in Tunisia in 2023 (average age: 10 +/− 3.9 years); Chérif et al [22] in Donka, Guinea in 2021 (mean age: 8 years); Diallo et al [23] This non-negligible difference between the averages could be explained by several factors: the difference in the research setting and the type of population, but also by the search for easy gain at a very early age by some victims, the low socioeconomic level, the sexual curiosity of boys their age and, above all, the lack of sex education among young people.…”
Section: Agecontrasting
confidence: 64%
“…Female Sexual Function Index (FSFI) questionnaire [18] To assess sexual functioning, we used the Female Sexual Function Index (FSFI) scale, validated in French in 2012 by Dargis L. et al in Quebec. It comprises 19 questions assessing 06 domains: desire (1, 2); arousal (3,4,5,6); lubrication (7,8,9,10); orgasm (11,12,13); satisfaction (14,15,16); pain (17,18,19).…”
Section: Measurementsmentioning
confidence: 99%